Kinerja Guru Bimbingan Konseling Dalam Penyusunan Rencana Program Layanan Melalui Pendampingan Supervisi Klinis - Karsono, Karsono (Manajemen Pendidikan, 2016)
This research is motivated by the unoptimally performance of teachers in a planning service program has so far not optimal. The research objective is to improve the performance of teachers in the planning service program in region Delanggu Klaten Working Group by 30 teachers. Methods of data collection using observation, documentation, and assignment of teachers in planning services program Analysis of data using a critical and comparative analysis. Indicators of success using the criteria limit minimal is 80, and the class completeness 100%. Research procedure uses cycles. From the results of research and discussion know that obtained summary data is the initial condition, Cycle I, II performance counseling teachers in planning services program, the initial conditions by an average of 75 and the first cycle an average of 80 and the second cycle by an average of 90 . from this data, it seems clear that an increase in the average value of the initial conditions to the first cycle of five digits (6.7%), from the first cycle to the second cycle an increase of 10 digits (12.5%), from pre cycle to the second cycle an increase of 15 digits (20%). The highest value of the initial stages of the condition by 84 and 90 as well as the first cycle of the second cycle of 98 It is clear that from the stage of initial conditions for the first cycle occurred from the initial conditions to the first cycle of six digits (7.1%), from the first cycle to the second cycle an increase of 8 digits (8.9%), and from the initial conditions to the second cycle an increase of 14 digits (16.7%). The lowest value obtained for the early stages of the condition of the first cycle of 67 and 72 and the second cycle of 87. thus, can be affirmed that the initial conditions of the stage to the first cycle an increase of 5 digits (7.5%), from the first cycle to the second cycle an increase of 15 digits (22.4%), and from the initial conditions to the second cycle an increase of 20 digits (29.9%). Percentage of performance criteria counseling teachers in preparing plan preparation program obtained from the initial conditions of 28% and the first cycle was obtained by 68% and the second cycle at 100%. It seems clear that the initial conditions of the stage to the first cycle an increase of 40%, from the first cycle to the second cycle an increase of 32%, and from the initial conditions to the second cycle an increase of 72%. Thus, teachers performance in counseling services from the initial conditions to the second cycle brought a significant rise.